P093 COMPARATIVE INCIDENCE OF INFLAMMATORY BOWEL DISEASE IN DIFFERENT AGE GROUPS: A COMMERCIALLY-INSURED, POPULATION-BASED US STUDY. (7th February 2019) - Keyashian, Kian; Dehghan, Melody; Sceats, Lindsay A; Kin, Cindy; Limketkai, Berkeley; Park, KT
Abstract: Background & Aims: Data on the incidence of inflammatory bowel disease (IBD) by age groups are available in countries outside of the United States (US) or localized populations within the US. We aimed to estimate the incidence rates (IRs) of IBD by age groups using a US multiregional dataset. Methods: We used the Optum® Research Database to identify incident IBD patients with a disease-free interval of 1.5 years between 2005-2015. Overall and age-specific IRs were calculated for 4 different age groups: pediatric (0-17 years), young adult (18-25 years), adult (26-59 years), elderly (>60 years). Time trends of incidence were evaluated in each age group. Disease extent and phenotype were also compared. Results: The mean IR for the cohort (n=60, 247) from 2005-2015 was 37.5/100, 000. The IR was highest in adult and elderly cohorts (36.4 and 36.7/100, 000 respectively), with predominance of ulcerative colitis (UC) over Crohn's disease (CD). The IR increased over the 10-year study period for all age groups (time trends p-value <0.001). The elderly group had more colonic and more stricturing CD phenotype but less perianal disease. In pediatric and young adult cohorts, the incidence for CD (5.2 and 11.8/100, 000 respectively) was higher than UC (2.4 and 9.6/100, 000 respectively), with a higher rate of penetrating CD. Conclusions: In one of the most comprehensive evaluations of the incidence of IBD in the US, we found a similar incidence rate to other national populations. We also confirmed differences of IBD phenotypes based on age groups, with less aggressive and lower rates of perianal disease in the elderly. Figure 1. Distribution of IRs for IBD in four different age cohorts.